2016
DOI: 10.1007/s10616-016-0015-x
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput AO/PI-based cell concentration and viability detection method using the Celigo image cytometry

Abstract: To ensure cell-based assays are performed properly, both cell concentration and viability have to be determined so that the data can be normalized to generate meaningful and comparable results. Cell-based assays performed in immuno-oncology, toxicology, or bioprocessing research often require measuring of multiple samples and conditions, thus the current automated cell counter that uses single disposable counting slides is not practical for high-throughput screening assays. In the recent years, a plate-based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…The manual method had a higher CV%, from 10% to 23%. The obtained results are in agreement with the results obtained by other authors using the manual method [11,17,30,31]. A comparison of the obtained linear interval and CV of Easycounter YC with other similar image cytometers showed that they have a similar CV, but the optimal interval is different for each different device: 1 Â 10 5 -2 Â 10 6 cells/mL with CV 3-10% for NucleoCounter YC-100 (company ChemoMetec) and 4 Â 10 6 -6.6 Â 10 7 cells/mL with CV 4-13% for Cellometer Auto X4 (10Â) (Nexcelom Bioscence) [11,23,28,31].…”
Section: Cell Count Linearity and Reliabilitysupporting
confidence: 92%
“…The manual method had a higher CV%, from 10% to 23%. The obtained results are in agreement with the results obtained by other authors using the manual method [11,17,30,31]. A comparison of the obtained linear interval and CV of Easycounter YC with other similar image cytometers showed that they have a similar CV, but the optimal interval is different for each different device: 1 Â 10 5 -2 Â 10 6 cells/mL with CV 3-10% for NucleoCounter YC-100 (company ChemoMetec) and 4 Â 10 6 -6.6 Â 10 7 cells/mL with CV 4-13% for Cellometer Auto X4 (10Â) (Nexcelom Bioscence) [11,23,28,31].…”
Section: Cell Count Linearity and Reliabilitysupporting
confidence: 92%
“…For example, when Acridine Orange and Propidium Iodide (AO/PI) are used for staining cells, AO permeates both live and dead nucleated cells, whereas PI enters only dead nucleated cells. As a result, all live nucleated cells fluoresce green and all dead nucleated cells fluoresce red, due to a phenomenon called as Forster resonance energy transfer or FRET [20]. RBCs are specifically not stained by AO/PI due to their lack of nucleus[21].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the Celigo Image Cytometer has been utilized to perform cell‐based assays in microplates by capturing and analyzing whole well images . In this work, the Celigo Image Cytometer was used to rapidly count sorted single cells in Greiner 96‐well half area plates in order to determine the sorting efficiency of the FACS.…”
Section: Methodsmentioning
confidence: 99%